Subtype-specific structural features of the hearing loss–associated human P2X2 receptor - Franka G. Westermann; Adam C. Oken; Philip K. E. Granith; Parthiban Marimuthu; Christa E. Müller; Steven E. Mansoor (Proceedings of the National Academy of Sciences, 2025)
The P2X2 receptor (P2X2R) is a slowly desensitizing adenosine triphosphate (ATP)-gated ion channel that is highly expressed in the cochlea. When mutated, the P2X2R exacerbates age- and noise-related hearing loss, but selective modulators of the receptor are lacking, and the molecular basis of activation and desensitization remains poorly understood. Here, we determine high-resolution cryoelectron microscopy structures of the full-length wild-type human P2X2R in an apo closed state and two distinct ATP-bound desensitized states. In the apo closed state structure, we observe features unique to the P2X2R and locate disease mutations within or near the transmembrane domain. In addition, our ATP-bound structures show how free anionic ATP forms subtype-specific interactions with the orthosteric binding site. We identify and characterize two different ATP-bound desensitized state structures, one similar to published models for other P2XR subtypes, and a second alternate conformation not previously observed. A loop adjacent to the orthosteric binding site between these two ATP-bound desensitized state structures undergoes significant conformational changes. These movements are supported by multireplicate, microsecond-scale molecular dynamics simulation studies and suggest a path by which ATP could enter or leave the orthosteric pocket. Together, our results provide structural insights into the P2X2R, facilitating structure-based drug development for this therapeutically important target.